Emotional intelligence as an object оf modern psychological reasearch (The Journal of Psychology and Sociology, 2012)
Emotional Intelligence, its structure and definition is considered. Emotional Intelligence within the broad context of self-motivation, emotions, self-regulation, stress-resistance and other traits of personality is presented. Decision making as a final stage of Emotional Intelligence process, as a processing of emotions and its personal meaning is defined.
Keywords: Emotional Intelligence; emotions; personal meaning.